PENERAPAN MODEL QUANTUM TEACHING DALAM PENINGKATAN HASIL BELAJAR GEOMETRI DI KELAS IV SEKOLAH DASAR - permanasari, dian (KALAM CENDEKIA PGSD KEBUMEN, 2014)
Abstract: Application of Quantum Teaching Models in Geometry Student Learning Outcomes Improved Fourth Grade Elementary School. This study aims to: (1) describe the learning steps Quantum Teaching in improving student learning outcomes, (2) identify obstacles and solutions in the application of models of Quantum Teaching Geometry in learning. This study is a collaborative action research conducted in three cycles. The results of this study indicate that the application of the Quantum Teaching by implementing measures Grow, Natural, Namai, Demonstrate, and Celebrate Repeat to improve student learning outcomes, the pre-action mastery percentage reached 24% of new students, having implemented measures student mastery percentage in cycle I to 86%, 90% cycle II and cycle III 95%. Application of Quantum Teaching models for learning Geometry encountered some obstacles, but these constraints can be solved by implementing improvement efforts as the solution of problems were encountered. Keywords: model Quantum Teaching, student learning outcomes, Geometry Abstrak: Penerapan Model Quantum Teaching dalam Peningkatan Hasil Belajar Geometri Siswa Kelas IV Sekolah Dasar. Penelitian ini bertujuan untuk: (1) mendiskripsikan langkah-langkah pembelajaran Quantum Teaching dalam upaya peningkatan hasil belajar siswa, (2) mengidentifikasi kendala dan solusi dalam penerapan model Quantum Teaching pada pembelajaran Geometri. Penelitian ini adalah penelitian tindakan kelas kolaboratif yang dilaksanakan dalam tiga siklus. Hasil penelitian ini menunjukkan bahwa penerapan model Quantum Teaching dengan menerapkan langkah-langkah Tumbuhkan, Alami, Namai, Demonstrasikan, Ulangi dan Rayakan dapat meningkatkan hasil belajar siswa, pada pra tindakan persentase ketuntasan siswa baru mencapai 24%, setelah dilaksanakan tindakan persentase ketuntasan siswa pada siklus I menjadi 86%, siklus II 90% dan siklus III 95%. Penerapan model Quantum Teaching dalam pembelajaran Geometri menemui beberapa kendala, namun kendala tersebut dapat terpecahkan dengan menerapkan upaya perbaikan sebagai solusi dari kendala yang muncul. Kata Kunci: model Quantum Teaching, hasil belajar siswa, Geometri